PERAN CAMAT SEBAGAI KOORDINATOR PEMBANGUNAN DI KECAMATAN KABUN KABUPATEN ROKAN HULU - Trinando T, Sondang; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Sub-district role as Development Coordinator in Kabun is not entirely without problems. This research found that there are problems occur such as the lack of coordination on doing development in Kabun Sub-district whether it is physical or non-physical. The problem formulation on this research is How is the role of Sub-district head as development coordinator in Kabun Sub-district Rokan Hulu Regency, and What factor that support and hamper the development the role of sub-district head as development coordinator in Kabun sub-district Rokan Hulu Regency.The purpose of this research is to understand the role of Sub-district head as development coordinator in Kabun Sub-district Rokan Hulu Regency and to understand the factors that support and hamper the role of Sub-district head as development Coordinator in Kabun Sub-district Rokan Hulu regency. This research is based on Kooznt theory about Koordination with planning elements, Communication, Division of Work and also Meeting/Conference.This research method is using descriptive qualitative approach. Informants on this research are the sub-district apparatus and people living in Kabun Sub-district. Data collection technique on this research are interview, observation, documentation, and qualitative analization.The results of this research are the role of Sub-district head as development coordinator in Kabun sub-district Rokan Hulu Regency is going well, as proven by sub-district head has done the development planning in kabun Sub-district according to procedure on planning process by conducting development planning conference. Other elements like communication on development coordination has been properly implemented and officials work according to their task and responsibility, also meetings about problem solving went according to sub-district’s agenda. The supporting dan hampering factors of sub-district head’s role as development coordinator are: Development of facilities and infrastructure to conduct coordination are insufficient. Limitation of human resource and budget insufficiency also become factors that hamper the role of sub-district head’s role as development coordinator.Key Words: Sub-district Head’s Role, Leadership, Coodination, and Development